Mengungkap Optimalisasi Kinerja Pegawai: Peran Budaya Kerja, Motivasi Kerja dan Kepuasan Kerja Sebagai Mediator - Siddiq Fahriady Seban; Rahmisyari Rahmisyari; Muh.Sabir Mustafa (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to explore the optimization of employee performance through the influence of organizational culture and work motivation, taking job satisfaction into account as a mediating variable. The research focuses on employees at the Representative Office of Bank Indonesia in Gorontalo Province, representing a public institution with high professional demands. The main issue addressed is the suboptimal employee performance despite the presence of established organizational cultural values and motivational efforts. A quantitative approach was employed using a causal explanatory design, involving the entire population of organic employees (n=35) as respondents. Data were collected through questionnaires and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results indicate that organizational culture does not significantly influence employee performance, either directly or through job satisfaction. In contrast, work motivation significantly affects job satisfaction but has no direct effect on performance. Job satisfaction is proven to fully mediate the relationship between work motivation and employee performance. These findings suggest that performance improvement cannot be achieved merely through cultural internalization or motivational efforts, but through the creation of work conditions that foster employees' psychological satisfaction. The conclusion emphasizes the importance of human resource management strategies focused on enhancing job satisfaction as a key to optimizing employee performance, while also contributing theoretically to the development of organizational behavior models in the public sector.